Conservation and Presentation of the Byzantine Period on the Historical Peninsula of Istanbul: Urban Archaeological Values in Ibrahim Pasha Palace and Imaret of Beyazit Complex - Karacay, Nese; Ciftci, Aynur (ISTANBUL UNIV, RESEARCH INST TURKOLOGY, DEPT ART HISTORY, 2023)
In the Historical Peninsula of Istanbul, which is a multi-layered settlement area, various values from different periods are found during the restoration works of historical buildings. The preservation of these discovered values together with the historical buildings, their presentation together, and incorporating them as a source of learning for the city's residents is an important topic that also interests experts from different disciplines. However, the inadequate presentation of these values prevents the integration of Byzantine layers into the city. Built in the 16th century, Ibrahim Pasha Palace was given the function of the Turk and Islamic Art Museum in 1966. The ruins of a Byzantine hippodrome were found during excavations in the courtyard. Built in 1505 and now used as a library, the Beyazit Complex Imaret started restoration works in 2012. As a result of excavations in the inner garden, remains of a semicircular church were found. Various investigations were carried out to determine the conservation and presentation problems of the Byzantine archaeological values in Ibrahim Pasha Palace and Beyazit Complex Imaret. The decisions of the regional conservation council on selected archaeological values were examined. A detailed assessment of the current condition of urban archaeological values has been carried out. In this study, information on the archaeological preservation and presentation of historical buildings during the restoration process is provided and recommendations are developed.
Keywords: Istanbul; Historical Peninsula; Byzantine; Urban Archeological Values; Preservation and Presentation; PRESERVATION; TRANSPARENCY; Art